Figments and Fragments of Mahayana Buddhism in India : More Collected Papers - Schopen, Gregory (Studies in the Buddhist traditions., 2005)
In these articles, Gregory Schopen once again displays the erudition and originality that have contributed to a major shift in the way that Indian Buddhism is perceived, understood, and studied.